2020
DOI: 10.1111/desc.13053
|View full text |Cite
|
Sign up to set email alerts
|

Development of spatial biases in school‐aged children

Abstract: In the adult brain, biases in the allocation of spatial attention can be measured using a line bisection task and are directly relatable to neural attention signals in the frontoparietal attention network. Behavioral studies on the development of spatial biases have yielded a host of inconsistent results, likely due to variance in sample size, definition of experimental groups, and motor confounds introduced by using a paperand-pencil version of a line bisection task. Here, we used a perceptual, computerized v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 51 publications
(73 reference statements)
0
7
0
Order By: Relevance
“…On the contrary, our results showed no evidence that biases change linearly during childhood when the mean age of the participants was entered as a moderator variable. However, the study with the youngest mean age was 5.6 years (De Agostini et al 1999), which is already within the age range where spatial biases are believed to emerge, and so we are unable to conclude whether children younger than this have a spatial bias (Bradshaw et al 1988;De Agostini et al 1999;Failla et al 2003;Girelli et al 2017;Hausmann et al 2003;Hoyos et al 2020;Patro et al 2018). We would encourage researchers to provide separate data for children at each year of age so that a more accurate picture of developmental trajectories in early childhood can be identified in future studies.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…On the contrary, our results showed no evidence that biases change linearly during childhood when the mean age of the participants was entered as a moderator variable. However, the study with the youngest mean age was 5.6 years (De Agostini et al 1999), which is already within the age range where spatial biases are believed to emerge, and so we are unable to conclude whether children younger than this have a spatial bias (Bradshaw et al 1988;De Agostini et al 1999;Failla et al 2003;Girelli et al 2017;Hausmann et al 2003;Hoyos et al 2020;Patro et al 2018). We would encourage researchers to provide separate data for children at each year of age so that a more accurate picture of developmental trajectories in early childhood can be identified in future studies.…”
Section: Discussionmentioning
confidence: 90%
“…2) Sex: Six studies reported separate data for girls and boys (Asenova and Andonova-Tsvetanova 2019;Chokron and De Agostini 1995;De Agostini et al 1999;Dellatolas et al 1996;Hoyos et al 2020;van Vugt et al 2000). Due to the small number of studies that reported separate data for boys and girls, we also calculated the percentage of male participants in each study where this data was available (11 studies did not report this data and were excluded from this analysis: Boles et al 2009;Dennis et al 2005;Girelli et al 2017;Hausmann et al 2003;Ickx et al 2017;Liu et al 2012;Michel et al 2011;Ninaus et al 2017;Roeltgen and Roeltgen 1989;Rolfe et al 2008;Sheppard et al 2002).…”
Section: Moderatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Hoyos et al. (2020) used a perceptual version of the horizontal line bisection task to understand the development of frontal‐parietal attentional networks. In this behavioral task, they found that participants marked the bisection point in an overall leftward direction.…”
Section: Introductionmentioning
confidence: 99%